The Movement Of Outermost Small Island Community Groups In Mangrove Conservation In The North Rupat District Bengkalis Regency - Susanti, Rina; Kadarisman, Yoskar; Asriwandari, Hesti; Putri, Oni Andriani (UNIVERSITAS PAKUAN, 2024)
Rupat Island is one of frontline islands in Riau Province. North Rupat district is one of islands that has a mangrove ecosystem covering 12,784 hectares. North Rupat’s geography, bordering and directly facing the Malacca Strait, makes it subject to abrasion, which frequently harm the mangrove environment that defends it. The objective of this study was to use a qualitative approach and SWOT analysis to examine the actions, opportunities, and difficulties faced by the outermost small island settlements in North Rupat District in mangrove conservation. Data was collected through in-depth interviews, observations, and Focus Group Discussions (FGDs). Purposive sampling was used to identify informants. The findings showed that five groups of outermost small island villages in North Rupat District conserve mangroves through the following actions: 1) raising awareness of the importance of mangroves, 2) conducting mangrove rehabilitation activities, 3) monitoring, and 4) developing ecotourism opportunities. Opportunities to assist the operation of the outermost small island community group movement in North Rupat included the potential for ecotourism in mangrove environments, which was able to increase the community’s economic level and have received BRGM support through nursery and planting programs. The obstacles faced included limited environmental knowledge and community participation, as well as the danger of abrasion disasters